07 Use of the dog-isolated cardiac Purkinje fibre assay to investigate a compound with in vivo proarrhythmic activity. Issue 1 (10th December 2010) - Graham, S; Wilson, C; Cui, Y; Heath, B
Abstract : The dog-isolated cardiac Purkinje fibre assay is commonly used to assess the electrophysiologic effects of drugs known to prolong the QT interval. Drug-induced QT prolongation can be associated with Torsade de Pointes arrhythmias. The aim of this study was to determine if the dog Purkinje fibre assay could distinguish between Compound A, which produced ventricular premature complexes (VPCs) in vivo in the dog via an unknown mechanism, and Compound B, which is from the same chemical and pharmacological class as Compound A but did not produce VPCs. Action potentials (APs) were recorded and the number of VPCs counted. Phase 4 slope, action potential duration at 60 and 90% repolarisation (APD60 and APD90), maximum rate of depolarisation (MRD) and resting membrane potential (RMP) were also measured and compared to time-matched vehicle control. Compound A at 100 and 300 μM produced VPCs in 6/8 fibres from 3/3 dogs ranging from 1≥50 VPCs during stimulation to 3–16 VPCs following discontinuation of stimulation (<30 s). In fibres with VPCs, Compound A significantly increased phase 4 slope at 100 μM. Compound A also significantly increased APD60 and APD90 at 30, 100 and 300 μM. In the Compound B group, only occasional VPCs were observed with a similar frequency to control. Compound B had no significant effect on phase 4 slope or the other AP parameters. In conclusion, the dog Purkinje fibre assay was able to distinguish between the proarrhythmic potential of Compound A and Compound B.